Extracorporeal biliary lithotripsy by shock waves - Petersen, Federico; Sojo, Enrique (Cirugía del Uruguay, 1992)
In this preliminary paper the authors state the physical principies of extracorporeal shock-wave biliary lithotripsy and the indications of this treatment in those patients who fu/fil/ the protoco/'s requirements.